Djuanda Declaration in the process of acknowledging Indonesia's maritime territory in the International World (1957-1982) - Metrahultikultura M; Risky Setiawan (Social Sciences, Humanities and Education Journal (SHE Journal), 2023)
The purpose of this writing is to review more deeply the factors that motivated the government of the Republic of Indonesia to issue the Djuanda Declaration in 1957, the Indonesian government's efforts to fight for the Djuanda Declaration to be recognized by the international community. The method in this research is the historical /historical method. As for the steps of the historical method are heuristics, source criticism which is divided into external and internal criticism, interpretation and historiography. This research uses a geographical, political, and economic approach through literature study. The results of the study revealed that geographical, historical, political, economic, social, as well as defense and security aspects were factors in the issuance of the Djuanda Declaration in 1957. The issuance of the Declaration was not immediately accepted by the international community, but had to be fought for by the governments of President Soekarno and President Soeharto until finally The United Nations Convention on the Law of the Sea recognized this Declaration in 1982. With the Djuanda Declaration, the territorial waters, land and air along with Indonesia and all of its contents stretching from Sabang to Merauke became integrated into the Unitary State of the Republic of Indonesia